2003
DOI: 10.1080/00241160310004657
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the tropics across land and sea: Permian to present

Abstract: The continuity through the past 300 million years of key tropical sediment types, namely coals, evaporites, reefs and carbonates, is examined. Physical controls for their geographical distributions are related to the Hadley cell circulation, and its effects on rainfall and ocean circulation. Climate modelling studies are reviewed in this context, as are biogeographical studies of key fossil groups. Low-latitude peats and coals represent everwet climates related to the Intertropical Convergence Zone near the Eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
192
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(208 citation statements)
references
References 88 publications
12
192
2
2
Order By: Relevance
“…As we have noted, fossil evidence indicates that tropical rain forest appeared after the K/T event in many areas where Late Cretaceous forests were apparently more open and dry adapted (Tiffney 1984;Wolfe 1987, 1993;Wolfe and Upchurch 1987;Wing and Boucher 1998;Morley 2000;Johnson and Ellis 2002;Ziegler et al 2003). Further expansion and taxonomic diversification of this biome took place during the Cenozoic.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As we have noted, fossil evidence indicates that tropical rain forest appeared after the K/T event in many areas where Late Cretaceous forests were apparently more open and dry adapted (Tiffney 1984;Wolfe 1987, 1993;Wolfe and Upchurch 1987;Wing and Boucher 1998;Morley 2000;Johnson and Ellis 2002;Ziegler et al 2003). Further expansion and taxonomic diversification of this biome took place during the Cenozoic.…”
Section: Discussionmentioning
confidence: 98%
“…They can be defined as having a stratified closed canopy, as receiving abundant precipitation, as experiencing equable temperatures, and as containing woody angiosperm species, at least in the understory (Richards 1996;Whitmore 1998;Morley 2000). During the past 20 years the view has become widespread that the expansion and diversification of this vegetation type occurred principally during the past 65 million years, following the mass extinction event at the CretaceousTertiary (K/T) boundary (∼65 Ma [Tiffney 1984;Wing and Boucher 1998;Morley 2000;Johnson and Ellis 2002;Ziegler et al 2003]; Cretaceous and Cenozoic timescales following Gradstein et al [1995] and Berggren et al [1995]). This hypothesis was initially supported by the rarity of large stems (Wheeler and Baas 1991;Wing and Boucher 1998) and large diaspores (Tiffney 1984;Wing and Boucher 1998) of angiosperms in the Cretaceous and by the marked increase in diaspore size in the Early Tertiary.…”
mentioning
confidence: 99%
“…Maritime proximity and orography help ensure high rainfall in Southeast Asia and Malesia regardless of vegetation type, although angiosperms still influence climate as transpiration over tropical forests shifts convection centres inland and away from over the oceans. African tropical forests are already relatively dry and seasonal owing to the broad tropical extent of continental highlands uplifted in the last 10 Myr (Partridge 1997) and larger latitudinal swings of the intertropical convergence zone (McGregor & Nieuwolt 1998;Ziegler et al 2003). However, South America, where effects are largest, represents more than 50 per cent of global tropical rainforest area (Morley 2000), and our results predict that replacement of angiosperms would reduce the area of ever-wet conditions within the Amazon basin by a factor of five.…”
Section: Resultsmentioning
confidence: 99%
“…Standard global climate models that are widely used by the climate science community are modified only in that non-angiosperm physiology is substituted globally for that of the angiosperms while maintaining modern vegetative biomass. The environmental impact of angiosperms would have been first felt in the Cretaceous, albeit with extensively debated timing, geography and ecology (Morley 2000;Ziegler et al 2003;Burnham & Johnson 2004;Jaramillo et al 2006). Although modelling of the effect of angiosperm evolution on Cretaceous climates is ongoing, the emphasis here is not on the specific climate regime in which they originated but on determining the significance of their elevated transpirational capacities for climate in general.…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis for resolving the conflict between molecular and fossil data (Feild et al 2004(Feild et al , 2009), mentioned in connection with Appomattoxia, is based on the fact that the terrestrial ANITA lines are "xerophobic" plants restricted to wet, shaded forest understory habitats and evidence that such habitats were rare in the Triassic and Jurassic, when climates were relatively arid across the tropics (Ziegler et al 2003). The ANITA lines make up less than 0.1% of living angiosperm species, and analyses by Magalló n and indicated that rates of angiosperm diversification were initially low and did not speed up until origin of the mesangiosperm clade.…”
Section: Implications For Pre-cretaceous History Of the Angiosperm Linementioning
confidence: 99%